2009
DOI: 10.1002/macp.200900350
|View full text |Cite
|
Sign up to set email alerts
|

Homo‐ and Co‐Polymers of Norbornene Containing Aryl‐ and Hetaryl‐Azo Dyes; Synthesis and Sensing Properties

Abstract: A series of polynorbornene homo‐ and copolymers containing aryl‐ and/or hetaryl‐azo dyes were prepared through ring‐opening metathesis polymerization (ROMP). Thermal studies indicated that the polymers were thermally stable up to 250 °C, and possessed glass transition temperatures ranging from 93 to 133 °C. In THF solutions, the aryl‐azo dye containing homopolymers, displayed λmax = 417 nm while the hetaryl‐azo dye containing homopolymers displayed λmax = 495 nm. The copolymers displayed a λmax that encompasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…As opposed to radical polymerization techniques, ROMP is a facile way to incorporate these units into polymers and therefore, a number of polynorbornenes with azo dyes (5) have been synthesized [48][49][50][51][52]. In Fig.…”
Section: Chemosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As opposed to radical polymerization techniques, ROMP is a facile way to incorporate these units into polymers and therefore, a number of polynorbornenes with azo dyes (5) have been synthesized [48][49][50][51][52]. In Fig.…”
Section: Chemosensorsmentioning
confidence: 99%
“…A wide range of suitable monomers has been copolymerized comprising (hetero)polyaromatic compounds [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], and more sophisticated functionalities like conjugated oligomers [34][35][36][37][38][39], triphenylmethane [40][41][42][43][44][45][46][47], azo [48][49][50][51][52], or polymethine [53][54][55][56][57] dyes. Even transition metal coordination compounds of aluminum [58,59], iron [60], zinc [61][62][63], ruthenium [64, 65], europium …”
Section: Polymethine Dyesmentioning
confidence: 99%
“…This behaviour was also observed for solution-phase acids. We have previously shown that azo dye polymers show potential as solid-state acid sensors, [32] this behaviour was also observed for compound 10. A solid sample of this complex was also exposed to HCl (g) and was observed to change to a deep purple colour; when exposed to NH 3(g) the purple colour changed back to orange which indicated that the azonium ion could be formed in the solid state.…”
Section: Resultsmentioning
confidence: 57%
“…The difference in thermal stability is due to the presence of the azo dye in polymers 19 and 20, since the azo group has been found to decompose at temperatures around 200 8C. [24] DSC showed that the polymers possessed glass transition temperatures (T g ) between 35 8C and 103 8C ( Table 2). As can be seen, the phenol containing polymers 18 and 20 possess higher T g s than polymers 17 and 19.…”
Section: Resultsmentioning
confidence: 99%
“…Previously we have shown that poly(norbornenes) containing azo dyes show potential for solid state pH sensors. [24] Polymers 19 and 20 were tested for visual identification of acid in the solid state. As solids, polymers 19 and 20 appeared as orange to reddish orange materials, but when exposed to HCl (g) the materials became purple in colour.…”
Section: Resultsmentioning
confidence: 99%